Determinants of Firm Value with Financial Performance as a Mediating Variable on the LQ 45 Index 2020-2023 - Anggreny Copricornilam Siahaan; Maria Goretti Kentris Indarti (Dinasti Publisher, 2025)
This study examines the effect of intellectual capital, which includes human capital (VAHU), structural capital (STVA) and relational capital (VACA), on firm value (PBV), with financial performance (ROA) as the mediating variable. The population of this study consists of companies listed in the LQ45 index during the period 2020-2023. A total of 160 companies were selected as the sample using the purposive sampling method. The results show that human capital, structural capital and relational capital partially have a positive and significant effect on financial performance. Further tests show that structural capital has a positive and significant effect on firm value, while human and relational capital have a positive but insignificant effect. Financial performance mediates the relationship between human, structural and relational capital positively and significantly on firm value. In this research, the leverage variable (DER) and firm size are also used as control variables and the results obtained show that leverage has a positive and significant effect on firm value, while firm size has a negative effect on firm value.